Análisis Bibliométrico sobre la Auditoría Tributaria en Web of Science - Kwan Chung, Chap Kau (2024)
The objective was to carry out a bibliometric analysis on the Tax Audit in Web of Science, 2024. 177 documents were analyzed with the following filters: keywords ("audit", "tax audit" and "taxation"), original open access articles, in English, Spanish and Portuguese between 2005-2024. VOSviewer was used to analyze categories of co-citations, co-occurrences and co-authorships. It is revealed that 98.3% of the articles are in English; Accounting Review stands out with about 463 citations and a total link strength of 21,110; the keywords "taxation" (53 mentions and 162 strong links) is the most popular; and England (56 documents) is the country with the highest production. It is concluded that research on Tax Audit tends to have increasing relevance in recent years and the phenomenon is related to tax policy and tax compliance. Finally, it is necessary to promote international collaborations and strengthen research production in less represented countries.